The photocatalytic degradation of bezacryl yellow in a presence of TiO2 - hydrodynamic contribution. (10th April 2019) - Khenniche, Lamia; Benissad-Aissani, Farida; Amrane, Abdeltif; Bouzaza, Abdelkrim; Fourcade, Florence; Favier, Lidia
A pilot installation was carried out in the research laboratory containing a photocatalytic reactor. It is intended to eliminate organic pollutants, including a textile dye [bezacryl yellow (BZY)] in the presence the P25 (TiO2 ) and the PC500 (TiO2 ). The degradation rates were influenced by both TiO2 and the lamps (UVC/UVA). Both P25 and UVA light were the most effective. Both pseudo-first-order and Langmuir-Hinshelwood models described accurately the dye degradation. The biodegradability of the solution was enhanced by photocatalytic treatment. The performance of the system was reached after completion of the hydrodynamic study of the installation by optimising the solution circulation rate. Hydrodynamic modelling was conducted using the residence time distribution program. The parameters derived from the RTD model were compared with those determined experimentally and used to diagnose hydrodynamic conditions. The results showed that the reactor is an arrangement of both one plug flow reactor followed by one stirred tank.